Tibial Infratubercle Anterior Closing-Wedge Slope-Reducing Osteotomy With Combined Revision Anterior Cruciate Ligament Reconstruction - Abreu, Ricardo; Aboulafia, Alexis; Dickschas, Jörg; Ollivier, Matthieu; Mansour, Alfred (Arthroscopy Techniques, 2025)
Elevated posterior tibial slope (PTS) has been identified as a risk factor for failure of primary and revision anterior cruciate ligament (ACL) reconstruction. Anterior closing-wedge slope-reducing high tibial osteotomy (ACW-SRO) has been shown to decrease PTS, decrease ACL graft strain, and decrease static anterior tibial translation. One approach is an infratubercle ACW-SRO, which preserves the tibial tubercle and extensor mechanism, allows for concurrent procedures, and reduces complications related to patellar height and/or tunnel placement. The purpose of this study is to present technical and planning tips that are critical to executing a successful infratubercle ACW-SRO. Preoperative planning, precise execution, and plate fixation are critical to avoid complications such as hinge fracture, neurovascular injury, and nonunion. This technique is a safe and effective option for patients with elevated PTS and failed ACL reconstruction, although further studies are needed to assess long-term outcomes.
CRIS-Team Scopus Importer:2025-10-03